Pengaruh Kesenangan Komunitas Merek dan Kepercayaan Komunitas Merek pada Kesetiaan Merek - , ALMIRA FARISA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research aims to identify the influence of brand community affect and brand community trust to brand community commitment, and brand community commitment to brand loyalty (repurchase intention, word-of-mouth, and constructive complaint). This research using primary data from the respondent, the members of Swift Owner at Kaskus community. The results demonstrated all hypotheses have been confirmed. The result of this research shows brand community affect and brand community trust positively influence toward brand community commitment, and brand community commitment positively influence brand loyalty (repurchase intention, word-of-mouth, and constructive complaint).